Use of bedaquiline in spinal osteomyelitis and soft tissue abscess caused by multidrug-resistant Mycobacterium tuberculosis: A case report - Andrea De Vito; Vito Fiore; Valentina Urru; Elena Bozzi; Nicholas Geremia; Elija Princic; Donatella Canu; Paola Molicotti; Riccardo Are; Sergio Babudieri; Giordano Madeddu (Brazilian Journal of Infectious Diseases, 2022)
Introduction: Spinal Tuberculosis (STB) represents between 1% and 2% of total tuberculosis cases. STB management remains challenging; the first-line approach consists of medical treatment, while surgery is reserved for patients with complications. No data regarding STB treatment with bedaquiline-containing regimens are available in the literature. Case description: Herein, we report the case of a 21-year-old man from Côte d'Ivoire with a multidrug resistance STB with subcutaneous abscess. After approval of the hospital off-label drug committee, we started bedaquiline 400 mg daily for two weeks, followed by 200 mg three times per week, for 22 weeks, associated with linezolid 600 mg daily, rifabutin 450 mg daily, and amikacin 750 mg daily (interrupted after eight weeks). During treatment, we performed a weekly EKG. No QT prolongation was shown, but inverted T waves appeared, requiring several cardiological consultations and cardiac MRI, but no cardiac dysfunction was found. After 24 weeks, bedaquiline was replaced with moxifloxacin 400 mg daily. The patient continued treatment for another year. We performed another computer tomography at the end of treatment, confirming the cure. Discussion: A salvage regimen containing bedaquiline proved effective in treating multidrug-resistance tuberculosis spinal infection without causing severe adverse effects. However, further studies are needed to evaluate better bedaquiline bone penetration and the correct duration of treatment with bedaquiline in MDR spinal tuberculosis.